Translation Dilemmas at the Hungarian Dance University - Emese Egey (Tánc és Nevelés, 2021)
The amount of documents for translation is constantly growing at the Hungarian Dance University. The present paper briefly outlines the basic principles and some of the results of translation studies as an independent discipline. It takes a glimpse into certain issues of translation ethics and translation techniques. Based on texts for translation at the University, several examples highlight translation challenges in general and creating (dance) terminology. A detailed section is devoted to the necessity of proofreading, revision and the importance of revising source language texts as well. A proposal urges to set up a translation workshop.